C. F. LOUIS LEIPOLDT (28 DES 1880- 12 APR 1947) - Otto, W. (Scientia Militaria - South African Journal of Military Studies, 2012)
Leipoldt's military career as medical officer during the period of the First World War Is discussed. The part which each of the triumvirate, namely Jan F. E. Celllers, Totlus and Lelpoldt played In the Anglo-Boer War is discussed. A connection in their background and careers Is drawn seeing that they portrayed the grief and sorrow of the war In poetry.